2010
DOI: 10.1093/eurheartj/ehq024
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cardiovascular events and all-cause mortality with central haemodynamics: a systematic review and meta-analysis

Abstract: Central haemodynamic indexes are independent predictors of future CV events and all-cause mortality. Augmentation index predicts clinical events independently of peripheral pressures, while central PP has a marginally but not significantly (P = 0.057) better predictive ability when compared with peripheral PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
917
7
73

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,262 publications
(1,019 citation statements)
references
References 30 publications
22
917
7
73
Order By: Relevance
“…3,4 However, concerns have been raised as to whether AIx is a reliable measurement of vascular compliance in the elderly 5,6 due to the curvilinear association between AIx and age. 6,7 Interestingly, findings have been contradictory regarding AIx as predictor of CVD where AIx has been associated with increased risk of CVD in highrisk populations 8,9 and in men, 10,11 while its use as a predictor in women 12,13 and in the general population is less certain. 13,14 The association between AIx and traditional CVD risk factors has been analysed in several studies with different methodology and various findings.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, concerns have been raised as to whether AIx is a reliable measurement of vascular compliance in the elderly 5,6 due to the curvilinear association between AIx and age. 6,7 Interestingly, findings have been contradictory regarding AIx as predictor of CVD where AIx has been associated with increased risk of CVD in highrisk populations 8,9 and in men, 10,11 while its use as a predictor in women 12,13 and in the general population is less certain. 13,14 The association between AIx and traditional CVD risk factors has been analysed in several studies with different methodology and various findings.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The AIx, a marker of wave reflection, is influenced by both the magnitude and the timing of the pressure wave reflected from peripheral sites to the aorta. 6 Accordingly, increased AIx has been associated with high rates of cardiovascular morbidity and mortality, 5,7 due to an increased left ventricular afterload. 8 Previous research has demonstrated that the AIx reduces following an acute bout of cycling exercise 9,10 and low-intensity leg resistance exercise in healthy young individuals.…”
Section: Introductionmentioning
confidence: 99%
“…1 For these reasons, central pressure has emerged as an important factor underlying the pathophysiology of cardiovascular disease, arguably more so than brachial (peripheral) BP. 2,3 Central aortic pressure is known to be influenced by the phenomenon of arterial wave reflections returning from the lower body, which can be quantified by augmentation index (AIx). 4,5 During each cardiac cycle, an incident wave generated from the left ventricular contraction in opposition to central aortic impedance travels distally along the arterial tree.…”
Section: Introductionmentioning
confidence: 99%